EVALUATION OF SERUM ZINC LEVELS IN HOSPITALIZED CHILDREN WITH ACUTE RESPIRATORY INFECTIONS - Singh, Gurnoor; Bhardwaj, Anand Kumar; Chauhan, Gauri; Singh, Vikramjot (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: ARI is the leading cause of mortality and a common cause of morbidity in children below 5 years. Zinc deficiency may increase the risk of respiratory tract infection. Zinc is thought to decrease susceptibility to acute lower respiratory infections by regulating various immune functions. The aim of study was to study serum zinc levels in hospitalized children with acute respiratory infections aged 2 month to 5 years. Material and Methods: Serum Zinc levels in a hundred children admitted with ARI were evaluated. Results and conclusion: Out of a hundred patients with ARI, 60% had below normal levels. Mean serum zinc levels were 70.27 + - 25.23 microgram/dl. Zinc levels in LARIs were significantly lower (P value<0.05) when compared to UARIs. There was no statistically significant correlation with age, gender, anemia and immunization status. Keywords: ARI, UARIs, LARIs, Zinc serum levels. Abbreviations: ARIs- Acute Respiratory Infections, UARIs- Upper Acute Respiratory Infections, LARIs- Lower Acute Respiratory Infections, NIS- National immunization Schedule